Methicillin-resistant Staphylococcus aureus nosocomial pneumonia: role of linezolid in the People's Republic of China - Lesher B; Gao X; Chen Y; Liu Z (Dove Medical Press, 2016)
Beth Lesher,1 Xin Gao,1 Yixi Chen,2 Zhengyin Liu3 1Pharmerit International, Bethesda, MD, USA; 2Pfizer Investment Co. Ltd, 3Department of Infectious Disease, Peking Union Medical College Hospital, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, People’s Republic of China Abstract: The burden of methicillin-resistant Staphylococcus aureus (MRSA) nosocomial pneumonia in the People’s Republic of China is high, with methicillin-resistance rates greater than 80% reported for patients with S. aureus pneumonia treated in intensive care units. Historically, vancomycin was the treatment of choice for patients with hospital-acquired MRSA infections. Recent evidence suggests that the minimum inhibitory concentration for vancomycin is increasing. Additionally, patients treated with vancomycin require monitoring of vancomycin trough concentrations and can develop nephrotoxicity. Linezolid is a treatment option for patients with hospital-acquired MRSA infections that can be administered either intravenously or orally. Analysis of data from a worldwide linezolid surveillance program initiated in the year 2004 shows no evidence of increasing linezolid minimum inhibitory concentrations. The clinical efficacy of linezolid for patients with gram-positive, including MRSA, nosocomial pneumonia, was evaluated in numerous studies. In general, results from these studies show higher or similar clinical success with no mortality difference for linezolid compared to vancomycin treated patients. Results from a Phase IV study enrolling patients with MRSA-confirmed nosocomial pneumonia suggest higher clinical cure rates for linezolid compared to vancomycin treated patients. Although acquisition costs are higher for linezolid compared to vancomycin therapy, evidence suggests similar overall medical costs. Cost-analysis results from a Chinese perspective show that linezolid dominated vancomycin therapy for MRSA nosocomial pneumonia in ~35% of bootstrap simulations whereas vancomycin dominated linezolid in less than 2% of bootstrap simulations. In summary, results from both clinical and economic studies, including studies conducted from a Chinese perspective, support the use of linezolid for the treatment of patients with MRSA nosocomial pneumonia. Keywords: anti-infectious, methicillin-resistance, nosocomial pneumonia, health economics